The significant impact of polydopamine on the catalytic performance of the carried Au nanoparticles. Issue 8 (10th December 2014) - Ma, Aijing; Xie, Yijun; Xu, Jie; Zeng, Hongbo; Xu, Haolan
Abstract : The polydopamine carrier causes the enrichment of methylene blue toward its surface, leading to the improved catalytic performance of the carried Au nanoparticles. Abstract : Mussel-inspired polydopamine catalyst carriers dramatically enhance the catalytic performance (∼450%) of Au nanoparticles in methylene blue reduction, which is attributed to the local enrichment mechanism caused by the favourable attractive interaction between the polydopamine and reactants.